2021
DOI: 10.1088/1361-6528/abea37
|View full text |Cite
|
Sign up to set email alerts
|

Computational insights into modulating the performance of MXene based electrode materials for rechargeable batteries

Abstract: MXene, a still-growing large family of two-dimensional (2D) materials, has aroused enormous attention in the scientific community. Owing to their high specific surface area, good electronic conductivity, stability, and hydrophilicity, MXene has found a wide application involving electromagnetic interference shielding, sensors, catalysis, and energy storage, etc. In the field of energy storage, MXenes are promising electrode materials for various metal-ion batteries and they are also effective anchoring materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 143 publications
0
20
0
Order By: Relevance
“…We also further investigated the effects of novel functional groups (S, Se, Cl, Br) on the structural properties of TMDs/Ti 3 C 2 heterostructures. Previous experimental studies [ 51 ] have shown that the Ti 3 C 2 X 2 (X = S, Se, Cl, Br) are the most stable when the surface functional groups of Ti 3 C 2 are located in the cavity centers of Ti atoms and aligned perpendicularly to the Ti atoms in the middle layer because of the site-blocked repulsion reaction between the C atoms and the surface functional groups. Therefore, in this work, when the surface of Ti 3 C 2 was terminated by functional groups (S, Se, Cl, Br) in MoS 2 /Ti 3 C 2 X 2 and MoSe 2 /Ti 3 C 2 X 2 heterostructures, we focused on the case that the functional groups are located above the hole center of the Ti atom and perpendicular to the middle Ti atom, as shown in Figure 2 a,b, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We also further investigated the effects of novel functional groups (S, Se, Cl, Br) on the structural properties of TMDs/Ti 3 C 2 heterostructures. Previous experimental studies [ 51 ] have shown that the Ti 3 C 2 X 2 (X = S, Se, Cl, Br) are the most stable when the surface functional groups of Ti 3 C 2 are located in the cavity centers of Ti atoms and aligned perpendicularly to the Ti atoms in the middle layer because of the site-blocked repulsion reaction between the C atoms and the surface functional groups. Therefore, in this work, when the surface of Ti 3 C 2 was terminated by functional groups (S, Se, Cl, Br) in MoS 2 /Ti 3 C 2 X 2 and MoSe 2 /Ti 3 C 2 X 2 heterostructures, we focused on the case that the functional groups are located above the hole center of the Ti atom and perpendicular to the middle Ti atom, as shown in Figure 2 a,b, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…1(b and d). 54 However, little literature reported H-functionalized MXenes, especially Zr 2 C and Hf 2 C. To determine the conguration of Hfunctionalized MXenes, three sites in Fig. S1(a) † are considered: a top site of the M atom (I), two top hexagonal hollow sites of the M atom (II), and the C atom (III).…”
Section: Resultsmentioning
confidence: 99%
“…† The lattice constants obtained in this study are similar to those obtained in previously reported literature for all O and OH functional groups. 54 Moreover, the total electron density of states (TDOS) for the bare and functionalized MXenes was calculated and is depicted in Fig. S4 † and 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations